Emissão estimulada e auto-organização em um sistema quântico dissipativo - Silva, Wendel Lopes da (2024)
We begin our work by developing the 3 possible approaches that we can take when dealing with the interaction of radiation with matter. We have the classical theory, which consists of the Lorentz model. Next, we have the Rabi model, which is a semi-classical theory where we treat the quantized atom and the classical electromagnetic field. And finally, the fully quantum model which is the Jaynes-Cummings (JC) model. We use the JC model to calculate the entire dynamics for a system formed by a 3-level atom in the Λ configuration and a photon in an electromagnetic field (chapter 2). We also calculate the transition probabilities, for the initial condition in which there is a photon in the field and the atom is in the ground state. In chapter 3, which contains our main results, we investigate the same atom Λ, inserted in an electromagnetic field, but now containing two photons. We analytically solve the non-perturbative dynamics of this atom. As an application, we study the dynamics of a quantum state purification. We evidence two-photon nonlinearities and stimulated emission by comparing our exact model with the approximate scenario where two cascading single-photon wave packets drive the atom.